Between Past and Future - 2/9
Continuation of Prof. Katherine Verdery’s speech (University of Michigan) within “Vulnerabilities of the New Democracies” which is the fourth conference panel of the international event organized by CEU and Maryland University entitled “Between Past and Future: The Revolutions of 1989 and the Struggle for Democracy in Central and Eastern Europe." Prof. Katherine Verdery is followed shortly by Prof. Gail Kligman (UCLA). After Prof. Gail Kligman’s speech the chairman of the panel John Lampe (Professor at the University of Maryland) introduces Prof. Kazimierz Poznanski (University of Washington) and he delivers his speech. Prof. István Rév (Professor at CEU and Director of OSA Archivum) and Prof. Miklós Haraszti (Hungarian Writer and Journalist) are next in presenting their speeches. After Prof. Miklós Haraszti who gave the last presentations of the panel, the floor is open for questions and comments from the audience.